Progressive dysembryoplastic neuroepithelial tumour. Issue 1 (January 2015) - Alexander, Hamish; Tannenburg, Anthony; Walker, David G.; Coyne, Terry
Abstract Dysembryoplastic neuroepithelial tumour (DNET) is a benign tumour characterised by cortical location and presentation with drug resistant partial seizures in children. Recently the potential for malignant transformation has been reported, however progression without malignant transformation remains rare. We report a case of clinical and radiologic progression of a DNET in a girl 10 years after initial biopsy.